“Prosperity and Modernity Now!” Self-Folklorization Dilemmas in Edward Redlinski’s Novel Awans - Tarnowska, Małgorzata (Literatura Ludowa. Journal of Folklore and Popular Culture, 2023)
The aim of the article is to consider the emancipatory dimension of self- folklorization – a category proposed by Ewa Klekot to define a strategy of regaining voice by subordinate subjects, understood as an important element of the processes of modernity. The material for the analysis of socio-cultural processes of the post-war period using this category consists in Edward Redliński’s novel Awans (Advancement, 1973), presenting the dilemmas of self-folklorization of inhabitants of a fictional socialist village in the context of post-war modernization processes. The analysis of this novel allows us to ask questions – firstly, about the emancipatory dimension of self-folklorization, and secondly, about the connections between Redliński’s work and social changes in the Polish People’s Republic in the second half of the twentieth century.